Early evidence of functional impairment due to respiratory exposure: coal mining in Paipa, Colombia - Juan M. Ospina D (Universidad de Antioquia, 2011)
Objective: to assess the arterial concentration patterns of oxygen, the tolerance to moderate exercitation, and some vital variables in a sample of asymptomatic coal workers during the six minute walking test (6mwt). Methodology: an observational, prospective study measuring the following variables in a sample of 72 coal workers: the walked distance during the 6 minutes walking test, oxygen arterial saturation levels (spo2), cardiac frequency, dyspnea perception, and arterial pressure. Temporal performance of the included variables was assessed using an estimation of averages and percentages with their corresponding confidence intervals at 95%. Hypothesis tests were contrasted using Student's t and Chi square tests. Results:the Basal sao2 mean was 94.3% (sd=1.86); the sao2 mean at the end of test was 92.27% (sd=2.03). An atypical pattern of arterial desaturation of oxygen was found. Such pattern appears at the start of the walking test and remains for the 6 minutes. This was associated with age, the time they spent working, and the underground working environment. No significant changes in arterial pressure levels were found. Conclusions: there was an atypical pattern of arterial desaturation of oxygen that suggests the presence of restrictive lung disease at an early stage of its development. This pattern is associated with the time subjects spent working and their ages. The 6 minute walking test may be a very appropriate diagnostic methodology for assessing and controlling work-related respiratory disease; especially when it is supported by the conventional respiratory function tests. It is necessary to develop and implement appropriate regulations regarding labor hygiene in coal mines.